Protecting location privacy in cloud services. (19th May 2022) - Kumar, Sarvesh; Srivastava, Prabhat Kumar; Pal, Atul Kumar; Mishra, Vinay Priy; Singhal, Prateek; Srivastava, Gaurav Kumar; Mamodiya, Udit
Abstract: In GPS system enabled hand-held communication devices which works as a beacon that transmits our location. Also, the location-based services that emerged in recent years make use of location data. The location data provided to these location-based service providers have enough sensitive information to bother about. The location privacy became an area of concern in recent years. Developed and developing countries are now in process to make laws against the use of location information without the consent of the user or without legal warrant. Most of the research strategies proposed in recent years have one thing in common that we provide a region instead of exact coordinates of the location of the user. These attacks are called location dependent attacks or velocity linkage attacks in literature. We have in our effort proposed a solution to the problem of location privacy protection taking care of the location dependent attacks. We also keep in mind the fact that user is more concerned about his locations at certain places. We tested the proposed solution against requests issued by 5000 and 15000 users moving in a field of 10000x10000 units' area.